Using snake and ladder games in teaching speaking skill to the nineth year students of SMPN 18 Surakarta - Rismasari; Luqman Al Hakim (Journal of English Language Proficiency, 2025)
Abstract The purpose of this study is to examine how the snake and ladder game can be utilized to teach English and enhance students' speaking abilities. Additionally, this study evaluates the classroom environment when these games are employed as teaching tools. This study used a two-cycle classroom action research approach. Beginning with the academic year in October 2023–2024, this study was carried out. Students from class IX A Smpn 18 Surakarta served as the study's subjects. Both qualitative and quantitative methodologies were used to gather the research data. While pre-test, post-test 1, and post-test 2 were used to gather quantitative data, observation, documentation, and questionnaires were used to get qualitative data. Miles and Huberman (1994) used the triangulation approach to analyze qualitative data, and the average test score was used to examine quantitative data. The outcomes demonstrated how well the snake and ladder game worked to help students become more fluent speakers. In the first test, the average score was 62, in the first and second final tests, it was 72 and 79, respectively. There was a noticeable improvement in the classroom setting; kids were more engaged, content, and cooperative during the teaching and learning process.